The Complementary Roles of Chloroplast Cyclic Electron Transport and Mitochondrial Alternative Oxidase to Ensure Photosynthetic Performance - Chadee, Avesh; Alber, Nicole A.; Dahal, Keshav; Vanlerberghe, Greg C. (Frontiers in Plant Science, 2021)
Chloroplasts use light energy and a linear electron transport (LET) pathway for the coupled generation of NADPH and ATP. It is widely accepted that the production ratio of ATP to NADPH is usually less than required to fulfill the energetic needs of the chloroplast. Left uncorrected, this would quickly result in an over-reduction of the stromal pyridine nucleotide pool (i.e. high NADPH/NADP+ ratio) and under-energization of the stromal adenine nucleotide pool (i.e. low ATP/ADP ratio). These imbalances could cause metabolic bottlenecks, as well as increased generation of damaging reactive oxygen species. Chloroplast cyclic electron transport (CET) and the chloroplast malate valve could each act to prevent stromal over-reduction, albeit in distinct ways. CET avoids the NADPH production associated with LET, while the malate valve consumes the NADPH associated with LET. CET could operate by one of two different pathways, depending upon the chloroplast ATP demand. The NADH dehydrogenase-like pathway yields a higher ATP return per electron flux than the pathway involving PROTON GRADIENT REGULATION5 (PGR5) and PGR5-LIKE PHOTOSYNTHETIC PHENOTYPE1 (PGRL1). Similarly, the malate valve could couple with one of two different mitochondrial electron transport pathways, depending upon the cytosolic ATP demand. The cytochrome pathway yields a higher ATP return per electron flux than the alternative oxidase (AOX) pathway. In both Arabidopsis thaliana and Chlamydomonas reinhardtii, PGR5/PGRL1 pathway mutants have increased amounts of AOX, suggesting complementary roles for these two lesser-ATP yielding mechanisms of preventing stromal over-reduction. These two pathways may become most relevant under environmental stress conditions that lower ATP demands for carbon fixation and carbohydrate export.